Menjaga ketersediaan temulawak sebagai bahan baku produksi jamu (studi kasus: Provinsi Jawa Timur) - Ernaning Widiaswanti; Nachnul Ansori; Mohammad Zaimuddin Hisyam (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Temulawak (Curcuma xanthorrhiza Roxb.) is a plant native to Indonesia with many benefits. The need for temulawak is increasing along with the increasing public awareness to consume traditional medicine instead of chemical drugs. It has led to increased demand for temulawak by the traditional medicine industry. The demand and supply of temulawak must be maintained to avoid oversupply scarcity. This study aims to build a simulation model of temulawak supply sustainability in East Java using a system dynamic approach and the ratio of supply and demand (S/D ratio). System dynamic modeling was chosen to model the condition of the temulawak availability system in determining medium-term strategies. System dynamic are very appropriate for simulating policies and evaluating the condition of the temulawak availability system. This study considered three scenarios: expanding temulawak land by 5%, increasing temulawak productivity to 20 kg/m2, and a combination of the first and second scenarios. The results showed that the most effective policy was scenario three, by combining the policy of expanding agricultural land by 5% and increasing temulawak productivity to 20 kg/m2, with this policy model being able to maintain the S/D Ratio 1 for the next 5 years.